Constructing "Old Spanish Days, Inc." in Santa Barbara, California, USA: Flamenco vs. Mexican Ballet Folklórico. (2014) - Hellier-Tinoco, Ruth
Abstract : Old Spanish Days Fiesta, an annual five-day event held in Santa Barbara, California, since 1924, "… provides an education to residents and visitors about the history, customs, and traditions of the American Indian, Spanish, Mexican, and early American settlers that comprise the rich cultural heritage of Santa Barbara" (http://www.sbfiesta.org ). Dance plays a central role, with flamenco in the spotlight as the prime corporeal practice, constructing Spanishness through romanticized and revisionist historiography, and validating European colonization, migration, and diaspora. Although Mexican ballet folklórico is also featured, given the socio-political context in relation to people of Mexican heritage (recent and long-term) in Santa Barbara, I argue that deliberately privileging flamenco as the principal dance perpetuates problematic divisions, validating Europe and simultaneously undermining a Mexican presence.